Heterogeneous Acupuncture Effects of Taixi (KI3) on Functional Connectivity in Healthy Youth and Elder: A Functional MRI Study Using Regional Homogeneity and Large-Scale Functional Connectivity Analysis - Linlu He; Guangxiang Chen; Ruwen Zheng; Yan Hu; Xiu Chen; Jianghai Ruan (Neural Plasticity)
Heterogeneous neurological responses of acupuncture between different groups have been proposed by previous studies but rarely studied. The study described here was designed to explore the divergence of acupuncture at Taixi (KI3) on spontaneous activity of brain regions and functional connectivity (FC) between healthy youth and elder with functional magnetic resonance imaging (fMRI). 20 healthy young volunteers and 20 healthy elders underwent 10-minute-resting-state fMRI before acupuncture, and then acupuncture at Taixi (KI3) for 3 minutes; after withdrawing the needles, volunteers underwent a second fMRI scan for 10 minutes. Regional homogeneity (ReHo) and large-scale FC analysis using Power 264 atlas were utilized to analyze the changes of brain spontaneous activity. Compared with the resting state, the decreased ReHo after acupuncture at KI3 in both groups were concentrated in the left postcentral, right paracentral lobule, and right SMA. Moreover, the subjects in the HY group showed declined ReHo in brain regions involving the right lingual and precentral. However, those subjects in the HE group presented decreased ReHo in the right postcentral and precentral, left supramarginal gyrus and SMA, and both cingulum middle after needling in KI3. Compared with the resting state, the HY group in the postneedling state showed lower mean intranetwork FC in sensory/somatomotor and subcortical network. And the internetwork FC between sensory/somatomotor and dorsal attention had significantly decreased after acupuncture. Furthermore, the internetwork FC between subcortical and dorsal attention and between subcortical and cerebellar showed the most obvious elevations after needling in the HY group. In the elder group, both FCs of internetwork and intranetwork primarily involving sensory/somatomotor, cingulo-opercular, and dorsal attention were declined after acupuncture. These results indicated that acupuncture at KI3 had heterogeneous acupuncture effects in different age groups. Our study led to converging evidence supporting the acupuncture effect segregation of different condition subjects and supporting evidence for prevention and treatment with acupuncture in the future.